Characterization of Biobriquette from A Mixture of Rubber Seed Shell Charcoal with Sugar Cane Bagasse Using Variations of Adhesive Types - Harmiansyah; Rifki Renaldi; Zunanik Mufidah; Nova Anika (Department of Mechanical Engineering, Universitas Andalas, 2025)
The use of energy, especially fossil fuels in the world, is increasing along with the increasing human population and increasing industrial development in various countries that use conventional energy. The way to reduce the use of conventional energy is to use renewable energy, one example of renewable energy is biobriquettes. Biobriquettes are solid fuels derived from the remaining organic matter that has undergone a compression process with a certain compressive force. The purpose of this study is to analyze the characteristics and determine the optimum parameters of biobriquettes from rubber seed shell charcoal and bagasse with variations in adhesives (tapioca flour, sago flour and molasses). The ratio of charcoal to adhesive mixture is 90:10, 85:15, 80:20. The stages of research on making biobriquettes include raw material preparation, carbonization, printing and product analysis. The results of the study showed that there were 2 characteristic parameters that met the standard values in all adhesive variations, namely moisture content and ash content, except for molasses adhesive variations with a ratio of 80:20 and the optimum parameters obtained in biobriquettes mixed with rubber seed shell charcoal and taboo pulp using tapioca adhesive with a ratio of 90:10 with a moisture content value of 4.53%, ash content 4.78%, flying substance content 31.33%, carbon content 59.36%, calorific value 4422 cal/g, combustion rate 0.097 g/min, and drop test 30.9%.